Sistem Pemantauan dan Kendali Kualitas Air Serta Deteksi Kebocoran Pipa Berbasis Internet of Things - Bariandi, Muhammad Rizki; Rismawan, Tedy; Suhardi, Suhardi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
PDAM is a local government-owned company responsible for providing drinking water and clean water services to the community. During the distribution process, the water delivered by PDAM sometimes does not meet good water quality standards. Solid particles in cloudy water can erode pipes, cause blockages, and ultimately lead to pipe leaks. Therefore, a system is needed to monitor water quality and pipe conditions, including automatic control of water turbidity and detection of pipe leaks. In this research, an Arduino Uno is connected to turbidity, pH, and pressure sensors. NodeMCU ESP32 is used to control the actuators and send sensor reading data to the Firebase database. The test results indicate that the average error for the turbidity sensor is 3.29%, for the pH sensor is 4.15%, and for the two pressure sensors when the pipe is not leaking, the average error is 0.88%. The system can also provide notifications on an Android application when there is a decrease in water quality or a pipe leak. The average time interval required for the system to send notifications to the Android application is 3.47 seconds.